Plasma-Spray Ionization (PLASI): A Multimodal Atmospheric Pressure Ion Source for Liquid Stream Analysis - Kaylor, Adam (2014)
A new ion generation method, named plasma-spray ionization (PLASI) for direct analysis of liquid streams, such as in continuous infusion experiments or liquid chromatography (LC), is reported. PLASI addresses many of the analytical limitations of electrospray ionization (ESI) and has potential for real time process stream analysis and reaction monitoring under atmospheric conditions in non-ESI friendly scenarios. In PLASI-mass spectrometry (MS), the liquid stream is pneumatically nebulized and partially charged at low voltages; the resultant aerosol is thus entrained with a gaseous plasma plume from a distal glow discharge prior to MS detection. PLASI-MS not only overcomes ESI-MS limitations but also generates simpler mass spectra with minimal adduct and cluster formation. PLASI utilizes the atomization capabilities of an ESI sprayer operated below the ESI threshold to generate gas-phase aerosols that are then ionized by the plasma stream. When operated at or above the ESI threshold, ionization by traditional ESI mechanisms is achieved. The multimodal nature of the technique enables readily switching between plasma and ESI operation. It is expected that PLASI will enable analyzing a wide range of analytes in complex matrices and less-restricted solvent systems, providing more flexibility than that achievable by ESI alone.